THE MALKINSKOYE POLYMETALLIC ORE DEPOSIT DEVELOPMENT PROJECT OF THE 1930s: A HISTORICAL ANALYSIS - Kuz'minov, Petr Abramovic; Gurtuev, Rasul Salihovic (History, Archeology and Ethnography of the Caucasus, 2025)
This article examines the historical trajectory of the Malkinskoye polymetallic ore deposit, located in the gorges of the Malka River and its tributaries within the Republic of Kabardino-Balkaria. The study encompasses the initial discovery of the deposit in 1915 by A.P. Gerasimov and the subsequent intensive investigations conducted throughout the 1920s and 1930s, a period marked by significant industrialization in the USSR. Leading engineers and geologists from national specialized scientific institutions participated in geological surveys and the formulation of a comprehensive development project, which included the planned construction of an electrometallurgical plant to process the Malkinskoye iron-chromium-nickel ore. Although scheduled for implementation during the Third Five-Year Plan (1938-1942), the outbreak of the Great Patriotic War prevented the realization of this plant construction project. Subsequently, neither the Soviet nor the Russian Federation governments revisited the initiative to establish a major metallurgical center on the Malka River. However, recent advancements in science-intensive technologies within ferrous and non-ferrous metallurgy, coupled with increased governmental and societal interest in the natural resource development of the North Caucasus, particularly Kabardino-Balkaria, have led to a renewed focus on this region. Plans are currently being formulated for the revival of previously abandoned mining and metallurgical operations in the North Caucasus (such as the Tyrnyauz Tungsten-Molybdenum Plant and the Sadon Lead-Zinc Plant), alongside the exploration of new deposits. These plans are being developed with consideration for contemporary environmental and technical standards and with the aim of benefiting local populations. This study argues that the historical experience of planning the Malkinskoye deposit’s development offers valuable insights, both theoretically and practically, for the successful exploitation of metals crucial to Russian industry, provided that state and local authorities accord this deposit due attention.
Keywords: North Caucasus; Kabardino-Balkaria; River Malka; Gerasimov; Pokshishevskyi; polymetallic ore deposits; project; electrometallurgical plant